Impact of campus living conditions on Chinese medical school students’ mental health during the COVID-19 campus lockdown: the chain mediating role of cognitive reappraisal and expression suppression - Zhang, Wei; Huang, Long; Xu, Fengyun; Liu, Hairong; Wang, Guoping (Frontiers in Psychiatry, 2023)
Objective: To investigate the effect of changes in campus living conditions related to the Corona Virus Disease 2019 (COVID-19) pandemic on medical school students' mental health status, to explore the mediating role of emotion regulation strategies, and to provide effective suggestions for promoting medical school students' mental health. Methods: A self-report questionnaire, an emotion regulation questionnaire (ERQ), and psychological questionnaires for emergent events of public health (PQEEPH) were used to interview 998 medical school students who experienced campus lockdowns during the COVID-19 pandemic. Results: The mean total PQEEPH score was 3.66 ± 3.06. The degrees of inconvenience in daily life and change in routine and expression suppression as an emotion regulation strategy were significantly positively correlated with all PQEEPH dimensions. Cognitive reappraisal was significantly negatively associated with depression, neurosis, obsessive-compulsive anxiety, and hypochondriasis (ps < 0.05). Cognitive reappraisal and expression suppression demonstrated a chain mediating role between the degree of inconvenience in life and mental health and between the degree of change in routine and mental health (F=32.883, 41.051, ps < 0.05). Conclusion: Campus lockdown management significantly impacts medical school students’ mental health. Extensive use of cognitive reappraisal and expression suppression can reduce students’ adverse psychological reactions during campus lockdowns to an extent.